Identifying EFL Learners’ Psychosocial Identity Orientation and its Relationship with their Interlanguage Pragmatic Achievement - Seidi, Ali; Nazari, Hosna; Bijanpoor, Hasti; Mirzaei, Maryam; Esmaeili, Soheil (Assessment and Practice in Educational Sciences, 2026)
Previous research has not analyzed the identity orientation of EFL (English as Foreign Language) learners based on the glocalization view of teaching English. Hence, the current study attempted to determine the identity orientation of EFL learners based on three identity orientations of global, local, and glocal. Next, it investigated the relationship between EFL learners’ identity orientation and their interlanguage pragmatic achievement. Using qualitative and quantitative methods, an EFL Learner Identity Orientation Questionnaire and a Pragmatic Performance DCT (Discourse Completion Test) were handed to 120 EFL learners. The data were analyzed through the Pearson correlation test using SPSS version 26. Findings indicated that EFL learners were mostly glocally oriented in terms of social identity orientation. The second most frequent identity was local and global identity orientation had the lowest frequency. The Pearson correlation test did not show a statistically significant correlation between having a global and local identity and pragmatic performance. However, a statistically significant correlation was seen between having a glocal identity orientation (r = .34, P <.01) and pragmatic performance.